2005
DOI: 10.1074/jbc.m410647200
|View full text |Cite|
|
Sign up to set email alerts
|

Sensitization of Taxol-induced Apoptosis by Curcumin Involves Down-regulation of Nuclear Factor-κB and the Serine/Threonine Kinase Akt and Is Independent of Tubulin Polymerization

Abstract: Taxol is the best anticancer agent that has ever been isolated from plants, but its major disadvantage is its dose-limiting toxicity. In this study, we report with mechanism-based evidence that curcumin, a nontoxic food additive commonly used by the Indian population, sensitizes tumor cells more efficiently to the therapeutic effect of Taxol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
168
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(182 citation statements)
references
References 45 publications
11
168
0
1
Order By: Relevance
“…July 2009 that pretreatment is a prerequisite to enhance cell sensitization to chemotherapy agents (34). Similarly, we found that pretreatment has a synergistic effect on Taxol cell sensitivity, but not on simultaneous treatment.…”
Section: Parthenolide Potentiates Chemosensitizationsupporting
confidence: 50%
See 2 more Smart Citations
“…July 2009 that pretreatment is a prerequisite to enhance cell sensitization to chemotherapy agents (34). Similarly, we found that pretreatment has a synergistic effect on Taxol cell sensitivity, but not on simultaneous treatment.…”
Section: Parthenolide Potentiates Chemosensitizationsupporting
confidence: 50%
“…However, the advantage of soluble inhibitors is that their delivery would be easier and more efficient than gene transfer. Small molecules that inhibit IKK activity have indeed been described, and some of these molecules have been shown to induce apoptosis in cancer cells (19)(20)(21)(31)(32)(33). However, compounds that inhibit IKK with very high affinities have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that paclitaxel and Vinca alkaloid activate InB kinase (IKK) activity during cancer cell apoptosis (17), which suggests that the activation of the NF-nB/IKKs signal may contribute to the microtubule-disrupting agent -induced apoptosis of solid tumor cells. Rearrangement of the h-tubulin cytoskeleton by microtubuledisrupting agents has been suggested as a mechanism underlying the nuclear translocation and activation of NF-nB (9,10,18). However, it is not clear whether NF-nB activation is a prerequisite for the induction of apoptosis; nor is it clear whether there is a relationship between microtubule polymerization disruption and NF-nB activation during microtubule-disrupting agent -induced cancer cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that microtubule disruption by colchicines, Vinca alkaloids, or nocodazole (depolymerization agents), or by paclitaxel, epothilone, or laulimalide (stabilization agents) modulate several gene expressions and the activities of protein kinases involved in cell cycle arrest and apoptosis (7,8). These protein kinases include Bcl-2, Cdc25C, survivin, myc, caspase, p34 cdc2 , Ras/Raf, protein kinase C/protein kinase A, and c-Jun NH 2 -terminal kinase in addition to nuclear factor-nB (NF-nB) (9,10).…”
Section: Introductionmentioning
confidence: 99%